Urban Heat Island Phenomenon in Penang Island, Malaysia - Hanapiah, Nur Aili Hanim (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2019)
Urban heat island is a serious phenomenon affecting human discomfort, health problem and increased pollution. A lot of initiative was taken to decrease its impact. However, as urban area is developed tremendously, this scenario is still a serious issue. This study attempted to identify occurring of urban heat island in Penang Island, MBPP area by using a method of temperature field observation. All the data obtained were analysed to get the temperature contour image by using ArcGIS 10.1 software through SPLINE techniques and CLIP. The results showed that showed the existence of the urban heat island at the MBPP area occurred between 7 a.m to 10 p.m. This phenomenon occured in congested area and during peak hour. The study concluded that heat island has increased yearly due to various factors such as increased of population and motor vehicles because of development, industrialization and urbanization.